Android Remote Control System using wireless connection. Issue 1 (1st December 2022) - Sujana, Ahmad; Lestari, Ninik Sri; Rosmalina,; Suhendi, Hendi; Abduh, Mohamad
Abstract: Remote door lock control using an android based Arduino. where homeowners can lock and unlock by controlling the door lock via a cellphone that is often carried everywhere. So it is hoped that a remote door locking system can be via a smartphone (smartphone) to assist in locking without having to go to the door. In addition to that, the software created is expected to make it easier for homeowners to lock the door without having to go to the door by controlling the door lock using a cellphone to make it easier to open and lock the doors. The method used is the method of data collection and system development methods. The method of data collection is the method of observation and literature study. While the system development method used is the waterfall method. Application control door locks remotely using Arduino based on android were modeled using UML diagrams (Unified Modeling Language). The conclusion of the application made can be used to lock and unlock the door of the house using a cellphone. The creation of an Android-based home door lock application can make it easier for homeowners to open the lock and homeowners are not afraid to lose their house keys. It is expected that the addition of features in the door lock control applications remotely using Arduino based on android not only controls the door lock.